Accumulation and Translocation of Heavy Metals by Acalypha wilkesiana Parts in the Phytoextraction of Contaminated Soil - Naseer Inuwa Durumin Iya; Zaini Bin Assim; Isa Bin Ipor; Ajoke Omonrinoye Omolayo; Isaac John Umaru; Binta Hadi Jume (Universitas Gadjah Mada, 2018)
This study was to investigate survival, growth and accumulation potential of Acalypha wilkesiana in phytoextraction of heavy metals contaminated soil. Acalypha wilkesiana was tested to evaluate its tolerance and phytoextraction capacity in soils contaminated with metals. It was tested under 10 mL of 100 mg/kg of As, Cr, Cd, Co, Cu, Fe, Mn, Ni, Pb, and Zn solution, along 240 days in greenhouse experiment with harvesting period of 60 days interval. Twenty four cuttings from Acalypha wilkesiana were subjected to the same treatment. Plants roots stem and leaves were dry-digested and analyzed using Atomic Absorption Spectrophotometer (AAS). Results show that Fe was the most accumulated metal followed by Cu, Mn, As and Zn with 5002.4, 542.7, 492.2, 396.7 and 308.2 mg/kg, respectively. The concentration of Cr, Ni, and Co was 101.2, 99.09, and 89.63mg/kg respectively. The highest concentration of Pb was 46.44 mg/kg, Cd was not detected by the plant. Bioconcentration Factor (BCF) of metals were above unity in root, stem, and leaf except for Fe which showed a value below the unity, and Pb shows highest BF value of 7.79. The Translocation Factor (TF) of Cr, Co, Fe, Ni, and Pb were higher, while that of As, Cu, Mn, and Zn were below the unity, Co showed the highest value of 15.93. Furthermore, Extraction Coefficient (EC) of Cr, Co, Ni, and Pb were greater than 1, while for remaining metals were lower than unity, the highest EC was observed from Pb with a value 17.21.